Anxious intellects : academic professionals, public intellectuals, and enlightenment values - Michael, John, 1953- (e-Duke books scholarly collection., 2000)
A critical examination of the complex role of intellectuals in contemporary society, including the often contradictory definitions of such roles advocated by intellectuals themselves.